Uma desigualdade do tipo Trudinger-Moser em espaços de Sobolev com peso e aplicações - Albuquerque, Francisco Sibério Bezerra (2014)
This work addresses a class of Trudinger-Moser type inequalities in weighted Sobolev spaces in R2. As an application of these inequalities and by using variational methods, we establish sufficient conditions for the existence, multiplicity and nonexistence of solutions for some classes of nonlinear Schrödinger elliptic equations (and systems of equations) with unbounded, singular or decaying radial potentials and involving nonlinearities with exponential critical growth of Trudinger-Moser type.